Engaging short film activity that supports learning, science identity, and nature of science comprehension - Amanda L. Molder; Emily Howell; Sarah Goodwin; Shannon Behrman; Stephanie Mathews (Journal of Microbiology & Biology Education)
ABSTRACT Improving perceptions of students' science identities and their understanding of the nature of science (NOS) are important learning goals for undergraduate biology students. Previous research has observed that students who reflect on personal histories and research narratives of diverse scientists experience positive changes in their own science identities and understanding of the nature of science, respectively. However, these stories were in written or mixed media formats (e.g., podcasts, TED talks). Here, we explore whether such stories in nonfiction film, an immersive storytelling medium, could also serve as an intervention in positively affecting these outcomes. The focus of our curricular intervention is two short films that explore personal histories and research narratives: Decoding Ancestral Knowledge and CRISPR Apostle. We assigned students (N = 286) in a large, asynchronous, online general microbiology course to watch Decoding and CRISPR at distinct times in the semester. Immediately after watching each film, students took a survey with closed- and open-response questions designed to measure content knowledge, science identity, and NOS learning. We analyzed quantitative responses using descriptive statistics and open-ended responses using a computational textual analysis method of structured topic modeling. Results indicate that watching the films had a considerable impact on content knowledge as well as students’ perceptions of scientists, self-identification as scientists, and understanding of NOS. Interestingly, there were some differences between the films on the degree of impact on science identity as well as the types of emergent themes for science identity and NOS. These results suggest that science nonfiction films with personal histories and research narratives can be useful tools in supporting these student outcomes. We describe in this article how to access these free materials, including the films, and also suggest possible modifications.